Risk factors for intracranial haemorrhage in patients with pulmonary embolism treated with thrombolytic therapy Development of the PE-CH Score - Chatterjee, Saurav; Weinberg, Ido; Yeh, Robert W.; Chakraborty, Anasua; Sardar, Partha; Weinberg, Mitchell D.; Kabrhel, Christopher; Barnes, Geoffrey D.; Mukherjee, Debabrata; Kumbhani, Dharam; Bashir, Riyaz; Vaidya, Anjali; Smith, Akaya; Fuchs, Barry; Groeneveld, Peter; Giri, Jay (Thrombosis and Haemostasis, 2017)
Pulmonary embolism (PE) is a major cause of morbidity and mortality world-wide, and the use of thrombolytic therapy has been associated with favourable clinical outcomes in certain patient subsets. These potential benefits are counterbalanced by the risk of bleeding complications, the most devastating of which is intracranial haemorrhage (ICH). We retrospectively evaluated 9703 patients from the 2003–2012 nationwide in-patient sample database (NIS) who received thrombolytics for PE. All patients with ICH during the PE hospitalisation were identified and a clinical risk score model was developed utilizing demographics and comorbidities. The dataset was divided 1:1 into derivation and validation cohorts. During 2003–2012, 176/9705 (1.8 %) patients with PE experienced ICH after thrombolytic use. Four independent prognostic factors were identified in a backward logistic regression model, and each was assigned a number of points proportional to its regression coefficient: pre-existing Peripheral vascular disease (1 point), age greater than 65 years (Elderly) (1 point), prior Cerebrovascular accident with residual deficit (5 points), and prior myocardial infarction (Heart attack) (1 point). In the derivation cohort, scores of 0, 1, 2 and ≥ 5 points were associated with ICH risks of 1.2 %, 1.9 %, 2.4 % and 17.8 %, respectively. Rates of ICH were similar in the validation cohort. The C-statistic for the risk score was 0.65 (0.61–0.70) in the derivation cohort and 0.66 (0.60–0.72) in the validation cohort. A novel risk score, derived from simple clinical historical elements was developed to predict ICH in PE patients treated with thrombolytics.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Embolism; thrombolysis; (intracranial) haemorrhage